PENERAPAN PEMBELAJARAN KONTEKSTUAL MELALUI PENGHAYATAN TERHADAP AL-ASMA ' AL-HUSNA - Muhammad Husni (Sekolah Tinggi Ilmu Tarbiyah Al - Ibrohimy Bangkalan, 2019)
Classroom action research, commonly called PTK, is a study conducted by teachers to improvethe process and results of classroom learning. This research has four stages, namely the planningstage, the action stage, the observation stage, and the reflection stage. The purpose of the study isto analyze and describe the learning process and results of each subject. The research methodsused by the method using qualitative and quantitative approaches. The qualitative approach isused to find out the learning process, while the quantitative approach is used to find out thelearning outcomes. The results of the study that the learning process of the subjects of Al-AsmaAl-Husna aqidah-akhlak using contextual methods increased, as did the Al-Asma 'AlHusna learning results showed an increase from each cycle.